[Spanish Translation] Limitations of Temporal (Forehead) Temperature Readings as a Screening Method for Covid-19 - Aragón-Vargas, Luis Fernando (2020)
As the Covid-19 pandemic continues to evolve, many countries are in the process of reopening schools, churches, and businesses. In an effort to screen for potentially infected individuals, temporal artery (forehead) temperature is measured in thousands of people each day. This editorial discusses some of the major limitations of this procedure as a screening method for Covid-19 and warns against the danger of the false sense of security that this practice may cause.